PERLINDUNGAN SAKSI DAN KORBAN TINDAK PIDANA KEKERASAN SEKSUAL - Ramadhani, Putri; Alzaifani, Muhammad; Utami, Shafira (Islamijah: Journal of Islamic Social Sciences, 2024)
Legal protection is very important for the people of the Republic of Indonesia. Because the state is very responsible for the violence experienced by the victim, which causes losses and suffering borne by the victim. This sensitive issue affects many women's lives, including crimes of sexual violence and sexual harassment. Protection is a form of action to prevent prolonged oppression of women. Efforts by legal protection institutions or advocacy institutions to create good law enforcement really need supporting factors so that legal protection can be created properly and effectively. Cases of sexual harassment can no longer be seen as ordinary cases because these cases no longer occur in urban areas but also in rural areas, causing trauma and a person's well-being. With that, trauma recovery is needed for someone who experiences or becomes a victim of sexual violenceKeywords: Legal Protection, Sexual Violence, Trauma Recovery